Results of a national survey of Australian nurses' practice caring for older people in an emergency department. Issue 19 (15th August 2016) - Deasey, Debra; Kable, Ashley; Jeong, Sarah
Abstract : Aim and objective: To report Australian nurses' practices caring for older people in the emergency department. Background: Unmet clinical needs of older patients in the emergency departments can have a negative impact on nurses and patients. Method and design: A national cross‐sectional survey using a previously validated instrument, Older Person in Acute Care survey, was conducted to measure Australian emergency nurses' attitudes towards older people in their care. Members of the College of Emergency Nursing Australasia (CENA) were invited to participate in the study. There were 371 (39%) completed and valid surveys returned. Results: This study determined that Australian emergency department nurses report many positive practices used for older patients in their care. Conclusion: In this study, the Older Person in Acute Care survey has identified that, overall, emergency departments nurses have positive clinical practices towards their older patients in the emergency departments. The implications for clinical practice are significant as patient centred care in the Australian emergency departments will reduce adverse events for the older patient.